Influence of Adding Empagliflozin to Conventional Anti-diabetic Therapy on Quality of Life Scale for Type 2 Diabetic Patients - Hadeel Delman Najim; Mohammed Mahmood Mohammed; Abbas Mahdi Rahmah (Iraqi Journal of Pharmaceutical Sciences, 2024)
To evaluate the efficacy of empagliflozin on the quality of life (QoL) and glycemic index in patients with type 2 diabetes mellitus (T2DM) inadequately controlled with conventional oral anti-diabetic agents (OADs). A pre-post study involved forty T2DM patients who were on a combination of three OADs (glimepiride + metformin + vildagliptin) with glycated hemoglobin A1c (HbA1c) 7.0% - 12.0%. All patients received empagliflozin (10 mg/day) as add-on therapy for 16 weeks. Adding empagliflozin showed significant reduction in postprandial plasma glucose (PPG), (HbA1c), body mass index (BMI) and index of central obesity (ICO) (p<0.001). Significant improvements have been shown in the Quality of Life in Iraqi type 2 diabetic patients (QOLSID) scores post-intervention (p<0.001). Besides, good QoL was reported in patients with lower BMI and among those who had DM for duration less than 10 years. The outcome of this study showed that empagliflozin as add-on to oral antidiabetic triple therapy in poorly controlled T2DM has achieved a better weight management, well glycaemic control and enhanced QoL through the therapy, and was well tolerated among the study sample. Keywords: Empagliflozin, Glycemic index, Quality of life, SGLT2 inhibitors, Type 2 DM.